Optimising geosynthetic clay liner overlaps: implications on hydraulic performance. Issue 4 (1st May 2019) - Weerasinghe, Isuri A; Gallage, Chaminda; Dawes, Les
Abstract : Geosynthetic clay liners (GCLs) play a major role in optimising the hydraulic performance of today's barrier systems. Numerous researches have been carried out to evaluate and enhance the hydraulic performance of GCLs. However, there are still challenges in maintaining consistent performance at roll overlaps. This paper reviews the studies conducted to determine the liquid flow mechanism through the overlap, methodologies developed to assess the hydraulic performance and also how different factors affect the performance at the overlap. The preferential flow at the overlapping seam has been identified as a critical factor affecting the hydraulic performance, and an emphasis on understanding the mechanism of the liquid flow is identified as important. Hence, the necessity of research to quantify the horizontal (transverse) flow in the overlap region is brought into discussion. A new development proposes a potential experimental and numerical method for quantifying the preferential flow and factors affecting it in the overlapping region of GCLs.